If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -10x = 47 + -38x Solving 7 + -10x = 47 + -38x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '38x' to each side of the equation. 7 + -10x + 38x = 47 + -38x + 38x Combine like terms: -10x + 38x = 28x 7 + 28x = 47 + -38x + 38x Combine like terms: -38x + 38x = 0 7 + 28x = 47 + 0 7 + 28x = 47 Add '-7' to each side of the equation. 7 + -7 + 28x = 47 + -7 Combine like terms: 7 + -7 = 0 0 + 28x = 47 + -7 28x = 47 + -7 Combine like terms: 47 + -7 = 40 28x = 40 Divide each side by '28'. x = 1.428571429 Simplifying x = 1.428571429
| 2(2x-1)=9 | | 3a^2-7a=20 | | y = -2x+6 | | 2(7x-(7-3y+6x)+2y)= | | Y+Y=24 | | 5x+34=17x+14 | | 5x+34=17x+18 | | 9x-4=-8 | | 8(u-8)=-5u-38 | | -10x-3(x-2)= | | 2y=9(4)-4x | | 10x+15=2x+21 | | 8(u-8)=-5-38 | | t^2+3t-10=0 | | 2x+5=-40-7x | | x/2-(2x+1)/6=(x+1)/3 | | 8(u-8)=-5lu-38k | | x(21-2x)(39-2x)= | | -10z^2+11z=3 | | 5t-(t-2)=2-3.(t-5) | | 71-6x=39x+21 | | 13-8x=173-36x | | 5x^2+8=2x | | 7(t+4)+3(2t-5)= | | 19-y=x-x | | 7(q+2)=7q+14 | | 2x+4x=21 | | =8+8 | | 2x=62 | | x+2(y-x)=5+x | | 4x+27=191 | | 5r^2-39r-8=0 |